Application of Methods for a Morphological Analysis of the Femoral Diaphysis Based on Clinical CT Images to Prehistoric Human Bone: Comparison of Modern Japanese and Jomon Populations from Hegi Cave, Oita, Japan. (7th June 2022) - Endo, Daisuke; Saiki, Kazunobu; Yoneda, Minoru; Ishida, Hajime; Ogami-Takamura, Keiko; Sakai, Rina; Murai, Kiyohito; Imamura, Takeshi; Naito, Yoshiatsu; Wakebe, Tetsuaki; Tsurumoto, Toshiyuki
Abstract : A morphological analysis of ancient human bones is essential for understanding life history, medical history, and genetic characteristics. In addition to external measurements, a three-dimensional structural analysis using CT will provide more detailed information. The present study examined adult male human skeletons excavated from Hegi cave, Nakatsu city, Oita Prefecture. CT images were taken from the femurs of adult males (Initial/Early Jomon Period (n = 10 ) and Late Jomon Period (n = 5 )). Cross-sectional images of the diaphysis from below the lesser trochanter to above the adductor tubercle were obtained using the method established by Imamura et al. (2019) and Imamura et al. (2021). Using Excel formulas and macros, the area of cortical bone, thickness, and degree of curvature were quantitatively analyzed. The results were compared with data on modern Japanese. The maximum thickness of cortical bone in the diaphysis and the degree of the anterior curvature were significantly greater in Late Jomon humans than in the other groups. In contrast to modern humans, the majority of Jomon femurs showed the S-shaped curvature with the medial side at the top position and the lateral side at the lower position. The present results demonstrate that Late Jomon humans had a wider range of activity than the other groups and also provide insights into diseases in the hip and knee joints of Jomon humans.